Um modelo abstrato de gerência de software para metodologias ágeis - Mallmann, Paulo Roberto (Universidade do Vale do Rio dos Sinos, 2011)
Nowadays a good project management has become a competitive factor in the market because it directly influences the quality of software. Many companies and organizations for the development of software invest in improving their development processes. However, the current market is requiring these companies to more quickly and adapt to highly dynamic business environments. To meet this reality emerged agile methodologies that support this new reality. However, current tools in project management more used does not have a solution that enables integrated planning of management activities and development activities. This deficiency of integration can result in distortions in the planning of projects causing delays in delivery of the software. Therefore, the objective was to create an environment management software that allows an agile project management software in a customized way in development environments that use concepts and characteristics of agile methodologies. To make this possible, we defined a modular dynamic model and covers all aspects related to project management and agile methodologies that can be instantiated by generating concrete models for each specific project. This dynamics model was given to the great advantage compared to other studies evaluated. Based on the proposed model was created a project management environment that exploited its full potential. This environment is supported by a set of software agents that maintain the upgraded concrete model. On the concrete model can be extracted and management reports gantt dynamic that makes them even more flexible so as to give the project manager and have a macro view of the progress of activities. In order to validate the proposed work, we performed a case study in a foreign company. The developed application was used during the development of a real project as a concrete result and brought greater security to project management. Its use enabled to detect failures quickly giving more time to adjust to the impacts on schedule, before being made only through individual conversations or meetings to follow up directly with the team.
Keywords: Metodologias ágeis; Gerência de projetos; Agentes de software; Engenharia de software; Agile methodologies; Project management; Software agents; Software engineering; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação